The sources of genomic diversity - Nelson, George (Henry Stewart Talks, 2007)
The sources of genomic diversity: DNA and mutation, effect of mutations, inheritance, selection and drift, Environmental diversity, Natural selection, Human genomic diversity, Population growth, G6PD, DNA and mutation: point mutations (SNPs) and more complex mutations, The effect of mutations: insertions or deletions and large chromosomal inversions, Translation, Coding mutations, The fate of mutations, Neural mutations, Deleterious mutations, Radically beneficial mutations: FOXP2, Sometimes beneficial/sometimes deleterious mutations: CCR5 delta-32 and Hgb S, Promoter mutations, Mutations traveling together: haplotypes